Multivariate Copula-based SUR Tobit Models : a modified inference function for margins and interval estimation - Silva, Paulo Henrique Ferreira da (Universidade Federal de São Carlos, 2015)
In this thesis, we extend the analysis of multivariate Seemingly Unrelated Regression (SUR) Tobit models by modeling their nonlinear dependence structures through copulas. The capability in coupling together the diferent - and possibly non-normal - marginal distributions allows the exible modeling for the SUR Tobit models. In addition, the ability to capture the tail dependence of the SUR Tobit models where some data are censored (e.g., in econometric analysis, clinical essays, wide range of political and social phenomena, among others, data are commonly left-censored at zero point, or right-censored at a point d > 0) is another useful feature of copulas. Our study proposes a modified version of the (classical) Inference Function for Margins (IFM) method by Joe & Xu (1996), which we refer to as MIFM method, to obtain the (point) estimates of the marginal and copula association parameters. More specifically, we use a (frequentist) data augmentation technique at the second stage of the IFM method (the first stage of the MIFM method is equivalent to the first stage of the IFM method) to generate the censored observations and then estimate the copula parameter. This procedure (data augmentation and copula parameter estimation) is repeated until convergence. Such modification at the second stage of the usual method is justified in order to obtain continuous marginal distributions, which ensures the uniqueness of the resulting copula, as stated by Sklar (1959)'s theorem; and also to provide an unbiased estimate of the copula association parameter (the IFM method provides a biased estimate of the copula parameter in the presence of censored observations in the margins). Since the usual asymptotic approach, that is the computation of the asymptotic covariance matrix of the parameter estimates, is troublesome in this case, we also propose the use of resampling procedures (bootstrap methods, like standard normal and percentile by Efron & Tibshirani (1993), and basic bootstrap by Davison & Hinkley (1997)) to obtain con_dence intervals for the copula-based SUR Tobit model parameters.
Keywords: Probabilidades; Intervalos de confiança; Bootstrap (Estatística); Cópula; Ampliação de dados; Método de inferência para marginais modificado; CIENCIAS EXATAS E DA TERRA; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::REGRESSAO E CORRELACAO